مبدأ شخصية العقوبة والمساواة فيها في الشريعة الإسلامية القانون الجنائي الإيراني أنموذجًا = The principles of individualization of punishments and equality of punishments in Islam: the Islamic punishment law in Iran as a sample - Salami, Faroogh; Arif, Arif Ali (Faculty of Syariah and Law at Universiti Sains Islam Malaysia (USIM), 2018)
يهدف هذا البحث إلى بيان "مبدأ شخصية العقوبة والمساواة فيها في الشريعة الإسلامية، وإتخاذ القانون الجنائي الإيراني أنموذجاً معتمدًا على المنهج الاستقرائي: باستقراء أقوال الفقهاء من المؤلفات المدونة حول هذا الموضوع، وكذلك بتتبع القوانين المتناثرة والبنود المتعلقة بمبدأ شخصية العقوبة والمساواة فيها إتخاذ القانون الجنائي الإيراني أنموذجًا، وكذلك الاعتماد على المنهجين التحليلي والمقارن: بتحليل هذين المبدأين ومناقشتهما. هذا، وقد وصل الباحث بالمناهج السابقة، واستنادًا إلى مفهوم العقوبة في الشريعة الإسلامية والقانون الجنائي الإيراني، أنها تتميز بخصائص مشتركة تستقل بها، ولا تشاركها فيها الجزاءات الأخرى، وهذه الخصائص أو الأصول الحاكمة على العقوبات تتمثل في مبدأ قانونية العقوبة، ومبدأ المساواة في العقوبة، ومبدأ شخصية العقوبة، والذي يركّز هذه الدراسة على المبدأين، مبدأ شخصية العقوبة، ومبدأ المساواة فيها، وقد تطرق في أثناء البحث إلى علاقة مبدأ شخصية العقوبة بتحمّل العاقلة الديةَ عن الجاني في الجنايات الخطئية، وإنه موافق للقياس (أي القواعد العامة والثابتة في الشريعة الإسلامية) وليس استثناء من مبدأ شخصية العقوبة. ******************************************************** The aim of this study isto review two principles of "individualization of punishments" and "equality of punishments" in Islam, and the topic wasinvestigated in the Islamic punishment law in Iran. The inductive method isused to study and induce the jurisconsults’ sayings and articles of law in the compiled writings on the related topic, and the two mentioned principles were analyzed using the analytical and comparative methods. Based on the mentioned methods and referring to the definition and concept of punishment in Islam and Iranian criminal law, the author concluded that punishments have common principles and properties which are dominant in all punishments and manifested in the principles of the legality of punishments, equality of punishments and individualization of punishments. Moreover, the author studied the relationship between the principle of individualization of punishment and paying blood money by the ‘Aqilah (blood relative/solidarity group) in unintentional crimes (error) and concluded that the Aqilah system is completely based on general and proved rules in Islam, and it is not excepted from the principle of individualization of punishment.